2022
DOI: 10.1021/acs.jmedchem.1c01855
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibitors of Medium-Size S1′ Pocket Matrix Metalloproteinases: A Stepping Stone of Future Drug Discovery

Abstract: Among various matrix metalloproteinases (MMPs), MMPs having medium-size S1′ pockets are established as promising biomolecular targets for executing crucial roles in cancer, cardiovascular diseases, and neurodegenerative diseases. However, no such MMP inhibitors (MMPIs) are available to date as drug candidates despite a lot of continuous research work for more than three decades. Due to a high degree of structural resemblance among these MMPs, designing selective MMPIs is quite challenging. However, the variabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 209 publications
0
9
0
Order By: Relevance
“…Beside their poor pharmacokinetics and low oral availability/inability, this major failure has been mainly attributed to their lack of specificity within the MMP family and towards other metalloenzymes. Benefiting from a better understanding of MMP biology that emphasizes the necessity to selectively target one single MMP in a given pathological context, a new generation of selective MMPi has emerged recently ( 131 ). To achieve a better selectivity, several strategies have been deployed.…”
Section: Mmps Adams and Cd95l Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Beside their poor pharmacokinetics and low oral availability/inability, this major failure has been mainly attributed to their lack of specificity within the MMP family and towards other metalloenzymes. Benefiting from a better understanding of MMP biology that emphasizes the necessity to selectively target one single MMP in a given pathological context, a new generation of selective MMPi has emerged recently ( 131 ). To achieve a better selectivity, several strategies have been deployed.…”
Section: Mmps Adams and Cd95l Regulationmentioning
confidence: 99%
“…To achieve a better selectivity, several strategies have been deployed. Regarding the small-molecule inhibitors they mainly consist in either replacing the hydroxamic acid group found in most of broad spectrum MMPis by a weaker Zn 2+ chelating moiety ( 132 , 133 ) or targeting exclusively the S1’ pocket which significantly differ between the MMPs ( 131 , 132 ). Alternatively, the development of surrogates of MMPs endogenous inhibitors such as TIMP analogs or targeting MMP gene expression using mRNAs have also been explored.…”
Section: Mmps Adams and Cd95l Regulationmentioning
confidence: 99%
“…Indeed, the small-molecule MMP inhibitors tested in clinical trials have shown uncertain efficacy and various side effects due to their poor selectivity. For this reason, selective MMP inhibitors have been actively investigated in recent years. Because the depth of the S1′ pocket differs among MMP subtypes, suitable S1′ pocket-binding groups for each subtype have been explored for MMP selectivity. …”
Section: Introductionmentioning
confidence: 99%
“…The study of the metalloenzymes in normal and pathophysiological conditions has elucidated several crucial involvements of these enzymes in a wide range of disease states, including cancer, neurodegenerative disorders, inflammation, osteoarthritis, cardiovascular diseases, viral and parasitic infections, as well as in epigenetic abnormalities. [1][2][3][4][5][6][7] Although several attempts were made to develop potential and selective inhibitors of such metalloenzymes, a few novel molecules have been approved to date for targeting such metalloenzyme-related pathophysiology and associated disease conditions. 8 Among these metalloenzymes, the Zn 2+ -dependent metalloenzyme meprin b is one of the metzincin superfamily proteases that modulates several substrates such as procollagen I, collagen IV, triggered receptor expressed on myeloid cells 2 (TREM 2), interleukin (IL)-6R, cluster of differentiation (CD) 109, CD99, MUC-2, amyloid precursor protein (APP), E-cadherin, and IL-1b.…”
Section: Introductionmentioning
confidence: 99%
“…The study of the metalloenzymes in normal and pathophysiological conditions has elucidated several crucial involvements of these enzymes in a wide range of disease states, including cancer, neurodegenerative disorders, inflammation, osteoarthritis, cardiovascular diseases, viral and parasitic infections, as well as in epigenetic abnormalities. 1–7 Although several attempts were made to develop potential and selective inhibitors of such metalloenzymes, a few novel molecules have been approved to date for targeting such metalloenzyme-related pathophysiology and associated disease conditions. 8…”
Section: Introductionmentioning
confidence: 99%